PENGARUH E-SERVICE QUALITY, E-TRUST DAN ARTIFICIAL INTELLIGENCE TERHADAP NASABAH EXPERIENCE PENGGUNA APLIKASI BRIMO - Kristhiofan, Karen; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to examine the effect of e-service quality, e-trust and artificial intelligence on the customer experience using the BRImo app in the DKI Jakarta area in 2022. This type of research is quantitative with the multiple regression analysis method using the SPSS tool. Based on the results of research on 100 respondents with a Likert scale of 1-4, it shows that e-service quality consists of reliability, responsiveness, assurance, empathy, and tangibles. E-trust, which consists of ability, benevolence, and integrity. Artificial intelligence which consists of mechanical intelligence, analytical intelligence, intuitive intelligence, and empathetic intelligence. These three variables have a significant influence on the Nasabah experience, which consists of immersion, flow, cognitive compatibility, and emotional compatibility. As a result, a higher level of nasabah experience will increase nasabah intensity when using the BRImo app.